Application of Structural Conditionality : 2009 Annual Report. (Policy Papers; Policy Paper ;, 2010)
Motivation and approach. Last year's major reforms of the Fund's lending instruments, together with the commitment to treble its resources, made a significant contribution to global stabilization as Fund lending created room for policy accommodation and helped countries weather the worst of the crisis. While these reforms have yielded positive results, it is appropriate to ask-as the IMFC has-whether there is scope to build on this experience. This paper tries to answer this question, including by drawing on the lessons of the crisis, as perceived by policymakers, market participants, and academic observers, with whom Fund staff has consulted extensively. While every effort has been made to explore the pros and cons of various reform options neutrally, some options are clearly more evolutionary (e.g., those building on last year's headline introduction of the Flexible Credit Line or FCL), while others are of a more radical nature (e.g., Fund provision of pure insurance payouts or collateralized lending). This paper focuses on the former, covering the latter set of ideas in a supplement. Once the Executive Board has had a chance to comment on all options, a more defined and specific set of proposals could be developed by staff for further consideration.